Joint association of estimated glucose disposal rate and body mass index with new-onset stroke - Yu, Ting; Shao, Da-Ming; Lv, Tian; Xiong, Yu-Jun (Frontiers in Neurology, 2025)
BackgroundStroke is a major global health concern, and understanding its modifiable risk factors is critical for prevention. Body mass index (BMI) and estimated glucose disposal rate (eGDR), indicators of adiposity and insulin sensitivity, respectively, are independently associated with stroke risk. However, the combined effects of these factors remain underexplored.MethodsThis study utilized data from the China Health and Retirement Longitudinal Study (CHARLS), including 7,212 adults aged over 45 years. Cox proportional hazards models assessed the independent and joint associations of BMI and eGDR with new-onset stroke. Mediation analysis evaluated BMI’s role in the eGDR-stroke relationship. Subgroup analyses by age, sex, and BMI categories were conducted.ResultsOver a 7-year follow-up, 587 participants (8.14%) experienced new-onset stroke. Higher BMI was positively associated with stroke incidence, while lower eGDR was linked to increased stroke risk. Participants with both obesity (BMI over 28 kg/m2) and lower eGDR faced the highest stroke risk (HR: 2.63; 95% CI: 1.78–3.89). Mediation analysis revealed that BMI significantly mediated 16.78% of the association between eGDR and new-onset stroke. Subgroup analyses showed consistent associations across age, sex, and BMI categories.ConclusionThis study highlights the significant and interconnected roles of BMI and eGDR in new-onset stroke risk, with a compounding effect observed in individuals with obesity and low eGDR. Addressing both insulin resistance and adiposity through targeted interventions could effectively reduce stroke risk, particularly in high-risk populations.